Omics in a Digital World: The Role of Bioinformatics in Providing New Insights Into Human Aging - Dato, Serena; Crocco, Paolina; Rambaldi Migliore, Nicola; Lescai, Francesco (Frontiers in Genetics, 2021)
Background: Ageing is a complex phenotype influenced by a combination of genetic and environmental factors. Although many studies addressed its cellular and physiological age-related changes, the molecular causes of ageing remain undetermined. Considering the biological complexity and heterogeneity of the ageing process, it is now clear that full understanding of mechanisms underlying ageing can only be achieved through the integration of different data types and sources, and with new computational methods capable to achieve such integration. Recent Advances: In this review, we show that an omics vision of the age-dependent changes occurring as the individual ages can provide researchers with new opportunities to understand the mechanisms of ageing. Combining results from single-cell analysis with systems biology tools would allow building interaction networks and investigate how these networks are perturbed during ageing and disease. The development of high-throughput technologies such as next-generation sequencing, proteomics, metabolomics, able to investigate different biological markers and to monitor them simultaneously during the ageing process with high accuracy and specificity, represents a unique opportunity offered to biogerontologists today. Critical Issues: Although the capacity to produce big data drastically increased over the years, integration, interpretation and sharing of high-throughput data remain major challenges. In this paper we present a survey of the emerging omics approaches in ageing research and provide a large collection of datasets and databases as a useful resource for the scientific community to identify causes of ageing. We discuss their peculiarities, emphasizing the need for the development of methods focused on the integration of different data types. Future Directions: We critically review the contribution of bioinformatics into the omics of ageing research, and we propose a few recommendations to boost collaborations and produce new insights. We believe that significant advancements can be achieved by following major developments in bioinformatics, investing in diversity, data sharing and community-driven portable bioinformatics methods. We also argue in favour of more engagement and participation, and we highlight the benefits of new collaborations along these lines. This review aims at being a useful resource for many researchers in the field, and a call for new partnerships in ageing research.